Electronic structures of organometallic complexes of f elements LXXIX: Truncated crystal field splitting patterns of monomeric pseudo trigonal planar Yb(η5-C5H4R)3 (R = Me, Et, tBu, SiMe3) complexes and polymeric [(η5-C5H5)2Yb(μ-η5:η1-C5H5)] as well as selected mono adducts - Amberger, Hanns-Dieter; Reddmann, Hauke; Liu, Guokui (Journal of organometallic chemistry, 2012)
The absorption spectra of pseudo (ψ) trigonal planar tris(methylcyclopentadienyl)ytterbium(III) (Yb(C5H4Me)3) have been recorded at room temperature and circa 77 K. The vibronic transitions were separated from the expected three purely electronic ones by correlating the transition energies with observed and assigned vibrational transition frequencies in the infrared spectrum. With this knowledge, the zero-phonon transitions in the absorption spectra of Yb(C5H4R)3 (R = Et, tBu, SiMe3) and [(η5-C5H5)2Yb(μ-η5:η1-C5H5)] (YbCp3), the latter being known since 1967, could be separated from phonon-assisted ones. The first low temperature luminescence measurements of an organometallic YbIII compound were performed by means of powdered YbCp3•THF and YbCp3•CNC6H11, respectively, and in both cases purely electronic and vibronic transitions were separated. The wavefunctions resulting from a fit of the truncated crystal field splitting pattern of YbCp3•THF allowed interpretation of the spectroscopic splitting factors g||/g⊥ and the temperature dependence of the paramagnetic susceptibility of this compound as well as the susceptibility anisotropy χ|| − χ⊥ of YbCp3•B (B = CNnBu, γ-picoline) and Yb(C5H4Me)3•B (B = CNtBu). The crystal field splitting pattern of the excited multiplet 2F5/2 of monomeric pseudo trigonal planar Yb(η5-C5H4Me)3 is extracted from the 77 K absorption spectrum which exhibits both vibronic and purely electronic transitions of comparable intensity. [Display omitted] ► Luminescence measurements of organometallic Yb compounds. ► Crystal field calculations of organometallic Yb compounds. ► Separation of vibronic and electronic transitions of organometallic Yb compounds.